UNRAVELLING THE RELATIONSHIP BETWEEN SMOKING AND THYROID STIMULATING HORMONE: HOW TOBACCO USE ALTER THYROID - Murad Tariq; Shayan Abid; Sadiq Umar; Hina Naz; Junaid Hameed; Madiha; Maria Seemab; Eeman Amir; Mansoor Ahmad Khan; Muhammad Hanif; Muhammad Nihal; Muhammad Umar; et al. (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: In order to understand the possible changes in thyroid function regulation brought on by tobacco use, this study explores the complex link between smoking habits and TSH levels. Methodology: This cross-sectional study included 160 individuals who were all chain smokers were included. And through purposive sampling technique they were divided into two groups: TSH Group 1, which included people with thyroid diseases that had been identified, and TSH Group 2, without such diagnoses. IRB approved the study and then blood samples were collected in Heparin gel tube and run in RMI laboratory (ISO certified), by using a Special Chemistry ELISA technique, samples were analyzed in less than eight hours to determine TSH levels. Results: Significant differences in TSH levels were seen between the two groups. 80 participants in TSH Group 1, 15 had below 0.4 uIU/ml TSH values, whereas the remaining 65 had normal TSH. On the other hand, out of the 80 participants in TSH Group 2, 23 had below 0.4 uIU/ml TSH and 57 had normal TSH values. Interestingly, mean TSH levels were greater in those with prior thyroid disease diagnosis than in people without prior thyroid disorder diagnosis with significant P value less than 0.05. Conclusion: Our study finds that those participants without having thyroid illness, smoking seems to make their thyroid dysfunction more serious, it’s interesting to note that in chain smokers without thyroid disorders, the mean TSH levels increased with age, from the 18–30 to51–60 age group